FEATURES OF DEVELOPMENT OF SOME ORGANS OF AIRBREATHING CATFISH (CLARIIDAE) IN EARLY ONTOGENESIS - A. V. Pirog; O. V. Lozhnichenko (Юг России: экология, развитие)
Aim. Airbreathing catfish (CLARIIDAE) - is one of the most promising specie of artificial breeding. However, for the reproduction of this specie it is required to conduct appropriate studies. In particular, it is necessary to review the features of morphogenesis during early ontogeny of this type of fish. We investigated prelarvae of airbreathing catfish (CLARIIBAE) in 2,3 and 4 days of life. In the embryos, the spinal cord was formed on the 2nd day of life. At this stage, organs of vision were sufficiently developed. On the 4th day, we found hyaline cartilage at the base of the gill arch, arcs were covered with gill filaments; we also discovered fully formed mesonephros, renal corpuscles, renal tubules and intratubular liquid in the kidneys. The heart of the embryo consisted of atrium and voluminous ventricle.Methods. The research of development of airbreathing catfish in early ontogenesis has been carried out on the basis of "RENTOP Agro-5" Ltd. under the conditions of RAS in the Krasnodar region in the spring – summer period of years 2013-14. For morphological analysis we used serial histological sections on prelarvae of 40 airbreathing catfish at age 2, 3 and 4 days developing normally and atypically. The research combines some complex biological methods: ichthyologic, histological, physiological. Materials for the research were handled with the methods of classical histology. Viewing and imaging of the sections were made using Mikmed 6 microscope with a digital camera for imaging and computer analysis.Results. The finding of the study has been the analysis of the morphological structure of airbreathing catfish during early ontogeny, which can contribute to improving the biotechnology of breeding of airbreathing catfish under RAS.Main conclusions. First, in the early ontogenesis of airbreathing catfish we have discovered heterochrony in the development of basic systems: rapidly developing central nervous system and the digestive system, cardiovascular system, respiratory and urogenital systems are formed more slowly. Second, we have revealed pathological abnormalities in the structure of the developing mesonephros which is the evidence of the need to adjust the breeding conditions.